Corps souffrants - Sandra Harrisson; Marie-Claude Thifault (Histoire, Médecine et Santé, 2021)
Our access to the patients’ medical record at the Montfort Hospital Mental Health Program (1976–2006), granted by the Research Ethics Office at Montfort Hospital and University of Ottawa, allowed us to discover sources that reveal the words, gestures and silences of women suffering from chronic mental illness. We were particularly interested in the sayings and writings of schizophrenic mothers who had lost custody of their children and found that over the years, this theme is recurrent in the interviews between patients and caregivers. The microhistorian approach selected is nourished by the works of Paul Ricoeur and Rita Charon, specifically, the role of health professionals in their sensitivity to capture the stories of their patients. The result of our analysis is presented in the form of a narrative construct that accounts for the double trauma experienced by a woman afflicted with a heavy syndrome in psychiatry and the consequences of this syndrome on her family life.